(untitled) (Per Musi, 2018)
The main objective of this paper is to investigate the derivative relations between the constituent elements of the theme of Arnold Schoenberg’s Orchestral Variations Op.31 and its source of basic material or Grundgestalt, a theoretical principle elaborated by the composer. After a bibliographical revision concerned with the origins and motivations for the formulation of the concept, the paper discusses the problematic issue of the presence of thematic development in Schoenberg’s serial music, taking as reference analyzes by some authors (RUFER, 1954; BOSS, 1992; HAIMO, 1997; TARUSKIN, 2010). It is also proposed that the Grundgestalt of a twelvetone piece can be manifested according to two levels, abstract and concrete, which adjusts to the analytical methodology adopted in this study, described in a specific section of the paper. The results obtained reveal an extraordinarily organic and economic thematic construction.